Return of 4U 1730–22 after 49 yr Silence: The Outburst Properties Observed by NICER and Insight-HXMT - Chen, Yu-Peng; Zhang, Shu; Zhang, Shuang-Nan; Ji, Long; Wang, Peng-Ju; Kong, Ling-Da; Chang, Zhi; Peng, Jing-Qiang; Shui, Qing-Cang; Li, Jian; Tao, Lian; Ge, Ming-Yu; et al. (Astrophysical journal. Letters, 2023)
After 49 yr of quiescence, 4U 1730–22 became active and had two outbursts in 2021 and 2022; the onset and tail of the outbursts were observed by NICER, which give us a peerless opportunity to study the state transition and its underlying mechanism. In this work, we take both the neutron star (NS) surface and accretion disk emission as the seed photons of the Comptonization and derive their spectral evolution in a bolometric luminosity range of 1%–15% L Edd . In the high/soft state, the inferred inner disk radius and the NS radius are well consistent, which implies that the accretion disk is close to the NS surface. For the decay stage, we report a steep change of the accretion disk emission within 1 day, i.e., the soft-to-hard transition, which could be due to the propeller effect, and the corresponding NS surface magnetic field is 1.8–2.2 × 10 8 G. Moreover, the inner disk radius is truncated at the corotation radius, which is similar to the propeller effect detected from 4U 1608–52. The absence of the propeller effect in the hard-to-soft state transition implies that the transition between the magnetospheric accretion and the disk accretion is not the sole cause of the state transitions.